ON THE TRACE FORMULA FOR A DIFFERENTIAL OPERATOR OF SECOND ORDER WITH UNBOUNDED OPERATOR COEFFICIENT - Gul, Erdal; Ucuncu, Duygu (YILDIZ TECHNICAL UNIV, 2018)
We consider the papers related to the spectrum and the trace formula of a differential operator of second order with unbounded operator coefficient. Reviewing them, we examine what the spectrum is and how to find the trace formula of the operator.
Keywords: Hilbert space; self-adjoint operator; kernel operator; spectrum; essential spectrum; resolvent; Engineering